Antithrombotic therapies for neurointerventional surgery: a 2021 French comprehensive national survey - Caroff, Jildaz; Aubert, Laurent; Lavenu-Bombled, Cécile; Figueiredo, Samy; Habchi, Kamelia; Cortese, Jonathan; Eugene, Francois; Ognard, Julien; Tahon, Florence; Forestier, Géraud; Ifergan, Heloise; Zhu, François; et al. (Journal of neurointerventional surgery, 2023)
BackgroundNeurointerventionists lack guidelines for the use of antithrombotic therapies in their clinical practice; consequently, there is likely to be significant heterogeneity in antithrombotic use between centers. Through a nationwide survey, we aimed to obtain an exhaustive cross-sectional overview of antithrombotic use in neurointerventional procedures in France.MethodsIn April 2021, French neurointerventional surgery centers were invited to participate in a nationwide 51-question survey disseminated through an active trainee-led research collaborative network (the JENI-RC).ResultsAll 40 centers answered the survey. Fifty-one percent of centers reported using ticagrelor and 43% used clopidogrel as premedication before intracranial stenting. For flow diversion treatment, dual antiplatelet therapy was maintained for 3 or 6 months in 39% and 53% of centers, respectively, and aspirin was prescribed for 12 months or more than 12 months in 63% and 26% of centers, respectively. For unruptured aneurysms, the most common heparin bolus dose was 50 IU/kg (59%), and only 35% of centers monitored heparin activity for dose adjustment. Tirofiban was used in 64% of centers to treat thromboembolic complications. Fifteen percent of these comprehensive stroke centers reported using tenecteplase to treat acute ischemic strokes. Cangrelor appeared as an emergent drug in specific indications.ConclusionThis nationwide survey highlights the important heterogeneity in clinical practices across centers. There is a pressing need for trials and guidelines to further evaluate and harmonize antithrombotic regimens in the neurointerventional field.